Preseason Y Balance Test Scores are not Associated with Noncontact Time-Loss Lower Quadrant Injury in Male Collegiate Basketball Players - Jason Brumitt; Kyle Nelson; Duane Duey; Matthew Jeppson; Luke Hammer (MDPI AG, 2018)
The Y-Balance Test-Lower Quarter has shown promise as a screening tool for identifying athletes at risk of injury. Subsequent studies, utilizing heterogeneous populations or different operational definitions of injury, have presented equivocal findings. Therefore, studies evaluating the efficacy of the Y-Balance Test to discriminate injury risk in a homogeneous population is warranted. One-hundred sixty-nine male (mean age 19.9 ± 1.5 y) collegiate basketball players were recruited during 2 consecutive seasons (2016–2017/2017–2018). Athletes completed the Y-Balance testing protocol at the start of each preseason. Athletic trainers tracked noncontact time-loss lower quadrant injuries over the course of the season. Receiver operator characteristic curves failed to identify cutoff scores; therefore, previously reported cutoff scores were utilized when calculating relative risk. There was no association between preseason Y-Balance Test scores and noncontact time-loss lower back or lower extremity injury in a population of male collegiate basketball players. This study adds to a growing body of evidence that demonstrates no relationship between preseason Y-Balance Test scores and subsequent injury.